ZnO Nanowires: Growth, Properties, and Energy Applications - Vincent Consonni (Nanomaterials, 2023)
As a biocompatible semiconductor composed of abundant elements, ZnO, in the form of nanowires, exhibits remarkable properties, mainly originating from its wurtzite structure and correlated with its high aspect ratio at nanoscale dimensions [...]